Testing dynamic balance in youth female volleyball players: development, reliability and usefulness - Karla Dolo; Zoran Grgantov; Igor Jelaska (Termedia Publishing House, 2022)
Purpose The aim of this research was to develop a dynamic balance test and examine its reliability by comparing first trial results with the average and best ones from multiple attempts. Methods Overall, 32 volleyball players (aged 11.3 ± 0.67 years) were investigated in 2 sessions (with a 14-day interval), each consisting of 3 trials of the modified bench walk with 3 turns (MBW3T) test. Three test methods were compared: first trial (MBW3T trial1 ), average result (MBW3T mean ), and best result (MBW3T best ). A paired-sample t -test determined differences with an effect size. Test-retest reliability was assessed with an intraclass correlation coefficient. Results The paired-sample t -test revealed no significant difference in performance between test and retest for MBW3T trial1 ( t = 0.01, p = 0.99), MBW3T mean ( t = -0.46, p = 0.65), and MBW3T best ( t = -1.05, p = 0.30). Standard error of measurement (SEM) as the absolute reliability within-individual variation parameter showed that MBW3T trial1 had higher variation than MBW3T mean and MBW3T best , in which the measurement error was minimal. To identify usefulness, we calculated the smallest worthwhile change and compared it with SEM for different effect sizes; the test was rated marginal to satisfactory. The study results indicated fair reliability when the first trial was observed and good reliability for the mean and best of 3 trials. Conclusions MBW3T mean and MBW3T best are cheap, simple, reliable, and marginal to satisfactory useful measures for assessing dynamic balance in youth female volleyball players and can be used in scientific and practical settings.